The status of diversity and species composition of crabs in navanthurai coastal area in jaffna peninsula of sri lanka - Tharmine, N.; Edrisinghe, U.; Sivashanthini, K. (University of Jaffna, 2014)
Crabs are economically important and a protein rich commodity in the coastal as well as offshore fisheries in Sri Lanka. Crabs are one of the potential aquaculture candidates and also form important commercial and recreational fishery. The present study was conducted with the aim of documenting the species composition and diversity of crabs inhabiting in the Navanthurai coastal area of Jaffna peninsula of Sri Lanka. The current investigation was carried out from November 2011 to October 2012 in Navanthurai coastal waters, which is a part of the Jaffna estuary situated between latitudes 9˚36’– 9˚50’North and longitudes 79˚ 40’– 80˚40’ East. Specimens were collected using different types of nets; mainly driftnet, gill net, hoop net and ‘Sirahuvalai’. All crabs were brought to the laboratory and identified up to species level based on the morphological characters. Accordingly, five edible species of crabs namely; Scyllaserrata, Portunus pelagicus, Thalamita craneta, Charybdis notator and Portunus sanguinolentes, belong to four genera of the family Portunidae were recorded. . Among them P.pelagicus is the dominant species contributing 93.5% followed by T.craneta and S.serratarepresenting 5.5% and1.5%, respectively. However, S.serrata is the most demanded species of crabs both for local and export markets. Only a few individuals of C.natator and P.sanginolentus were observed representing 0.37% and 0.13%,respectively of the harvest. The information and observations in this study will be of use in formulating management policies for the crab fishery off the Navanthurai coastal area.
Keywords: Coastal waters; crab; estuary; species composition